Potato genes protect rice - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
A gene taken from the potato and put into rice plants will help rice to defend itself against chewing insects. Insects, such as stem-borers, eat their way down the stem of the rice plant using enzymes called proteinases to digest what they have...